2013
DOI: 10.1186/1478-7954-11-22
|View full text |Cite
|
Sign up to set email alerts
|

Age-period cohort analysis of AIDS incidence rates in Rio de Janeiro, Brazil, 1985–2009

Abstract: IntroductionThe long average incubation time from HIV infection to AIDS makes it difficult to estimate the recent tendencies of HIV from AIDS incidence data. The objective of this study was to investigate the effects of three temporal components in AIDS incidence in the state of Rio de Janeiro, Brazil - age, period, and cohort.MethodsAge-specific AIDS incidence rates per 100,000 from Rio de Janeiro (Brazil) were calculated for both sexes using five-year age classes from 1985 to 2009 based on reported data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, the results from age-specific joinpoint regression analysis indicated that in the last three decades, women were bearing a significantly higher burden of HIV incidence than men. These findings are in line with the instances from South India and South Africa where a declining incidence of HIV infection was observed; however, the incidence is higher among males than females ( 28 , 33 , 34 ). Yet, it should be noted that a persistent HIV/AIDS epidemic may prompt risk reduction behavior in survivors after the passing of close family members in the family, neighborhood, or community ( 32 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the results from age-specific joinpoint regression analysis indicated that in the last three decades, women were bearing a significantly higher burden of HIV incidence than men. These findings are in line with the instances from South India and South Africa where a declining incidence of HIV infection was observed; however, the incidence is higher among males than females ( 28 , 33 , 34 ). Yet, it should be noted that a persistent HIV/AIDS epidemic may prompt risk reduction behavior in survivors after the passing of close family members in the family, neighborhood, or community ( 32 ).…”
Section: Discussionsupporting
confidence: 90%
“…The highest incidence of HIV infection was observed among the 1955–1959 birth cohort among males and the 1960–1964 birth cohort among females. Decreasing rates of incidence of the disease have been observed in people born between 1950 and 1964 in Spain and Brazil ( 33 , 49 ). The decline in the incidence rates at younger ages is indicative of the effectiveness of prevention options as a national response ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rodrigues (2013) detected similar trends in older people in Rio de Janeiro City, Brazil from 1985–1995 [24]. A study performed on injection drug users aged 15–65 years in Spain detected increasing trends in disease rates in men born between 1950 and 1962 and in women born between 1950 and 1964.…”
Section: Discussionmentioning
confidence: 90%
“…Among these limitations, we highlight the changes in the case definition of AIDS through time [12], the deficiency in the coverage of the epidemiologic surveillance system [24], slow data processing, underreporting, the high number of deaths without defined cause and inadequate death certificate completion. In addition to the cases that were not reported, data in this study excluded asymptomatic infected individuals because these data are not yet available in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Brazilian studies have shown that men have shown 2-3 times greater risk of AIDS occurrence than women 30,31 and the peak of AIDS incidence was around 2002 in Rio de Janeiro State 31 . Apratto Junior et al 30 , detected in elderly people of Niterói a peak of AIDS incidence around 2004.…”
Section: Discussionmentioning
confidence: 99%